KECERDASAN VERBAL LINGUISTIK PADA PENERAPAN DUA BAHASA DALAM PEMBELAJARAN DI SEKOLAH DASAR NAHDLATUL ULAMA KRATON KENCONG JEMBER - Mukni'ah Mukni'ah (Jurnal Asy-Syukriyyah, 2021)
The bilingual program is a language intelligence improvement program having a focus to use two languages in the teaching and learning activities at school. This article aims to describe the listening, speaking, reading, and writing skills of students in the application of two languages in elementary schools learning. This study was carried out at the Nahdlatul Ulama Elementary School in Kraton, Kencong Jember. The approach used in this study is qualitative with the type of case study research. Purposive method was used in subject selection. The data were collected through observation, interviews, and documentation. The data was analyzed by using the interactive analysis of the Miles and Huberman models which consisted of data condensation, data presentation, and drawing conclusion. The validity of the data was checked through triangulation of sources and techniques. The results of this study indicate that: (1) The students’ listening ability was done interactively in grades one and two which can be categorized as excellence: (2) The ability to speak interactively of students in grade one is carried out by role playing activities and in grade two is carried out by discussing activities about attitudes towards friends and presenting the results of the discussion in front of the class. (3) The reading ability of students is implemented in learning through reading aloud. (4) Students' writing skills are carried out through reviewing activities or summarizing using imaginative strategies.